About the psychology of religion and spirituality - Salgado Lévano, Cecilia (2016)
This paper aims to provide a systematic review of what comprises the psychology of religion and spirituality, for this first definitions, conditions and dimensions of religion, secondly, definitions and dimensions of religiosity are reviewed and thirdly, definitions, health models, dimensions and characteristics of spirituality. It is concluded that despite advances in this field, it is still necessary to allocate personal and collective efforts to promote research, given the undeniable role that the life of the human variables such as religious coping, spiritual conviction, spiritual, experiences and forms of religious participation, and spiritual beliefs and religious practices, conversion and faith in God.